EFFECTS OF DIFFERENT COOKING METHODS ON THE BIOACTIVITIES OF SOME SPICES - Chan, Eric Wei Chiang; Chan, Hor Jeann; Lim, Joo Ee; Yik, Sook Han; Tan, Su Fun; Yap, Pik Yee; Yap, Kim Yee; Yee, Siew Ying (Emirates Journal of Food and Agriculture, 2015)
In this study, the antioxidant, anti-tyrosinase, antibacterial and anti-quorum sensing (QS) properties of selected spices, and the effects of microwave, blanching and boiling were analysed. Of the spices screened for antioxidant properties, clove had the highest values followed by cinnamon with poppy having the lowest values. In general, cinnamon, star anise and cumin showed declines in antioxidant properties following cooking but clove and cardamom showed increases. Leaching of phenolic compounds into the water during blanching and boiling was most evident in cumin and cardamom. Of the six spices screened, cinnamon and cumin had the strongest anti-tyrosinase activity. Microwave (1 min) resulted in a significant loss in activity for clove and star anise. For microwave (5 min), a significant gain in activity was observed in cardamom. In general, the anti-tyrosinase activity of the spices remained unchanged following blanching and boiling. Of the five spices screened for antibacterial activity, clove showed broad-spectrum inhibition. Cardamom and cinnamon were only effective against Gram-positive bacteria. Cinnamon only inhibited Escherichia coli after cooking. Clove and cinnamon showed anti-QS activity against Chromobacterium violaceum with violacein inhibition zones of 15 and 9 mm, and minimum inhibitory doses of 0.5 and 2 mg/disc, respectively. The activity was retained after heat treatment. Besides the culinary benefits of spices, this study has demonstrated their therapeutic benefits even after cooking.